Social Pathology of Jakarta Society in Brian Khrisna's Novel Sisi Tergelap Surga - Sri Wahyunita Latonga; Asna Ntelu; Herman Didipu (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Social pathology is behavior that does not conform to social norms and can be detrimental to both individuals and society. This study examines the portrayal of the metropolitan lifestyle, forms of social pathology, causal factors, and impacts in Brian Khrisna's novel "The Darkest Side of Heaven." The research aims to describe the urban lifestyle in the novel, identify the forms of social pathology, explain the factors causing deviance, and outline the consequences. This study uses a Sociology of Literature approach that emphasizes the reciprocal relationship between literary works and social reality, and Burlian's Social Pathology theory as a foundation for examining the types of deviance, its triggers, and consequences. The method used is descriptive, with data consisting of novel excerpts representing the metropolitan lifestyle and the phenomenon of social deviance. Data was collected through literature review, then analyzed through a process of filtering, thematic grouping, interpreting meaning, and drawing conclusions based on the research findings. The results indicate that this novel presents four portraits of a metropolitan lifestyle that reflect urban society's orientation toward self-image, prestige, and symbolic success. Furthermore, five forms of social pathology were identified: crime, gambling, prostitution, alcohol consumption, and thuggery. Factors causing deviance include dysfunctional family conditions and economic pressures that push individuals to take shortcuts. The impacts are divided into two: those on the perpetrator, such as the loss of future, dignity, and self-control, and those on the environment, such as social unrest, decreased harmony, and weakened solidarity. Through its portraits of lifestyles, forms of deviance, causal factors, and impacts, this novel showcases complex social dynamics and the relationship between individuals and urban society.